Characterization of microbial community composition, antimicrobial resistance and biofilm on intensive care surfaces - Khalid Johani; Danya Abualsaud; Dayane M. Costa; Honghua Hu; Greg Whiteley; Anand Deva; Karen Vickery (Elsevier, 2018)
Background: Organisms causing healthcare associated infections can be sourced from the inanimate environment around patients. Residing in a biofilm increases the chances of these organisms persisting in the environment. We aimed to characterise bacterial environmental contamination, genetically and physiologically, and relate this to general intensive care unit (ICU) cleanliness. Methods: Cleanliness was determined by adenosine triphosphate (ATP) measurements of 95 high-touch objects. Bacteriological samples were obtained from the same sites (n = 95) and from aseptically removed sections (destructive samples, n = 20). Bacterial enrichment culture was conducted using tryptone soya broth prior to plating on horse blood agar, MacConkey agar, and screening chromogenic agar for identification of multidrug resistance organism (MDRO). Bacterial load and microbial diversity were determined using quantitative PCR (qPCR) and next generation DNA sequencing respectively. Confocal laser scanning microscopy and scanning electron microscopy were used to visually confirm the biofilm presence. Results: Many intensive care surfaces (61%) were highly contaminated by biological soil as determined by ATP bioluminescence testing. The degree of biological soiling was not associated with bacterial contamination as detected by qPCR. Bacterial load ranged from 78.21 to 3.71 × 108 (median = 900) bacteria/100 cm2. Surface swabs from 71/95 sites (75%) were culture-positive; of these 16 (22.5%) contained MDRO. The most abundant genera were Staphylococcus, Propionibacterium, Pseudomonas, Bacillus, Enterococcus, Streptococcus and Acinetobacter. Biofilm was visually confirmed by microscopy on 70% (14/20) of items. Conclusion: Bacterial biofilms and MDROs were found on ICU surfaces despite regular cleaning in Saudi Arabia, suggesting that biofilm development is not controlled by current cleaning practices. Keywords: ICU, ATP, Biofilm, Microbial community, Antibiotic resistance